Services Technology and Management: A Comprehensive Review - Chauhan, Pawan (Journal of Advanced Research in Public Policy and Administration, 2023)
The field of Services Technology and Management (STM) has emerged as a pivotal force in the 21st-century global economy, mirroring the profound shift from a manufacturing-centric paradigm to one dominated by services. This comprehensive review explores the multifaceted world of STM, providing a deep dive into its historical evolution, core concepts, emerging trends, and far-reaching implications. STM's evolution is traced through key milestones, from the rise of the service economy to technological advancements, globalization, and the imperative of customer-centricity. Its interdisciplinary nature, bridging technology, management practices, and societal dynamics, is illuminated as a fundamental aspect of its character. Key concepts within STM, such as service systems, service innovation, and service design thinking, are dissected, providing a foundational understanding of the field. Emerging trends, including digital transformation, service automation, and sustainability, reveal the dynamic forces shaping the future of services. The implications of STM extend beyond economic growth to encompass workforce transformation, ethical considerations, and the imperative of environmental sustainability. STM serves as a guiding light, illuminating the path forward for businesses, individuals, and policymakers in an era marked by constant disruption and evolution, where services stand as the linchpin of progress and prosperity.